Heterofonik Türk Makam Müziginde İşitsel Melodi Kestirimi - ŞİMŞEK, BERRAK ÖZTÜRK (Enstitute of Electrical and Electronics Engineers Inc., 2021)
In this study, the Improved Variable Mode Decomposition Method (IVMD) is proposed for the estimation of the audio melody in heterophonic works that constitute the general texture of Turkish maqam music. In our study, the fundamental frequencies of the records belonging to huzzam, kurdilihicazkar, ussak, and rast maqams were estimated by using the IVMD method. Since the basis of the heterophonic texture is that the same melody is performed by more than one instrument, the estimated fundamental frequencies are more than one for each time window. After the multiple frequency estimation, in order to obtain the audio melody of the music recording and therefore a single frequency line, the selection of the frequencies belonging to the audio melody line from the fundamental frequencies was made. The study has been compared with the methods widely used in the analysis of polyphonic music works such as YIN and MELODIA. When the comparisons were evaluated on the basis of maqam and mixture according to the MIREX criteria, successful results were obtained with the IVMD method. © 2021 IEEE.
Audio Melody Extraction From Heterophonic Turkish Maqam Music
Keywords: Improved Variational Mode Decomposition; Audio Melody Extraction; Heterophony; Melodi Kestirimi; Heterofoni